2002
DOI: 10.1046/j.1365-2524.2002.00379.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of blood pressures in Gemlik District, north-west Turkey

Abstract: The objectives of the present study were to evaluate the prevalence, awareness and control of hypertension among individuals over 30 years of age and to plan a follow-up programme for the same age group. A community-based sample of 1992 individuals (952 men and 1,040 women) was selected randomly. Out of the total study population, 1,388 (69.7%) individuals had normal blood pressure according to World Health Organisation criteria (systolic blood pressure < 140 mmHg and diastolic blood pressure < 90 mmHg), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(11 reference statements)
6
11
1
Order By: Relevance
“…Similar results have also been reported in studies conducted in Turkey (10,12,13,22). HT prevalence was higher in older ages also in the studies conducted by Arslantaş et al (22) (>50 years old, 59.5%), and Lai et al (26) (>60 years old; 53.09% in men, 56.06% in women).…”
Section: Womensupporting
confidence: 88%
See 4 more Smart Citations
“…Similar results have also been reported in studies conducted in Turkey (10,12,13,22). HT prevalence was higher in older ages also in the studies conducted by Arslantaş et al (22) (>50 years old, 59.5%), and Lai et al (26) (>60 years old; 53.09% in men, 56.06% in women).…”
Section: Womensupporting
confidence: 88%
“…Although in various studies conducted in Turkey and other countries have shown that, the prevalence of HT was higher in women than men (7,10,12,13,22,23) in some other studies HT prevalence is more prevalent in men than women (8,24). In our study, gender was a significant risk factor for HT; women had more HT risk than men (31.3% in women, 14.1% in men).…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations